Effect of Shrub Encroachment on Alpine Grass Soil Microbial Community Assembly - Dengzeng, Zhuoma; Ma, Wenming; Wang, Changting; Tang, Sihong; Zhang, Dong (Frontiers in Soil Science, 2022)
Shrub encroachment is a common phenomenon in grasslands all over the world. However, little is known about the consequences of shrub encroachment on soil microbial community structure in different layers. We investigated the effects of three common shrub encroachment (Potentilla fruticosa, Spiraea alpina, and Caragana microphylla) on grassland soil bacterial communities at the surface and deep layers in Qinghai–Tibetan Plateau. 16S rRNA gene sequencing was used to investigate the bacterial communities, and Fourier translation infrared spectroscopy (FTIR) was conducted to assess the soil organic carbon (SOC) chemical composition in surface and deep layers of shrub-encroached alpine grassland. Shrub encroachment has significantly increased SOC degradation in deep layer. After shrub invasion, the bacterial alpha-diversity in the surface and deep soil was higher than in grassland soil (except for the surface layer of C. microphylla). Factors driving bacterial community changes in soil surface and deep layer were different. Among the soil properties that were measured, SOC content was the primary factor that altered soil bacterial community composition in surface soil, while SOC chemical composition (aromatic and polysaccharides) was the main driver in the deep layer. A total of 39 and 42 biomarkers were found by linear discriminant analysis (LDA) effect size (LEfSe) in the surface and deep soil layer among the four sampling groups, respectively. Phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) showed that the most abundant predicted functional genes belonged to categories of metabolism (52.83%) in the primary metabolic pathway. Redundancy analysis (RDA) results also showed that the key factors affecting bacterial metabolic function appear to be SOC, pH, and aromatics, which are largely consistent with those affecting community composition. We suggest that shrub encroachment affect the structure, diversity, and predicted functions of bacterial communities, thus affecting the C cycle in this region.